Kapasitas Petani Kakao Bekas Penambang Batu Bara di Kota Sawahlunto - Delki Utama Asta; Aida Vitayala S Hubeis; Anna Fatchiya (Jurnal Penyuluhan, 2015)
The study aims to: (1) analyze the capacity of cocoa farmers ex-coalmining in Sawahlunto and (2) analyze factors that corrrelated with the capacity of cocoa farmers ex-coalmining in Sawahlunto. This research used survey method and was conducted in Sawahlunto City, West Sumatera on Desember 2014-February 2015. Numbers of sample this research are 70 respondents and used descriptive and correlational rank Spearman analysis. The results of this research showed that: (1) capacity of cocoa farmers ex-coalmining in production, marketing, farming management, problem solving and enviromental adaptation process was low, and (2) low capacity of cocoa farmer ex-coalmining in Sawahlunto correlated with formal education of farmers that only until elementary school, farming experience of farmers is still limited so their knowledge and skill to farm is low , extension support to give information for farmer is not maximal, the role of farmer groups to help farmers seeking farming information is still low and local goverment support to facilitating the needs of farmers is not optimal.Keywords: capacity, coalmining, cocoa farmer, extension support